1-Benzyl-3-[(4-methoxyphenyl)imino]indolin-2-one - Omobola A. Odedokun; Adebomi A. Ikotun; Chijioke J. Ajaelu; Nattamai Bhuvanesh (IUCrData, 2023)
The title compound, C22H18N2O2, is a Schiff base obtained by condensing p-arnisidine (4-methoxyaniline) with N-benzylisatin (1-benzyl-1H-indole-2,3-dione), which crystallizes in the triclinic P\overline{1} space group. The benzyl and phenyl rings subtend dihedral angles of 76.08 (7) and 60.70 (6)°, respectively, with the isatin group. The imino C=N double bond exists in an E conformation.